(untitled) (International journal of artificial intelligence, 2025)
The article discusses the main areas of work on the development of speech of deaf preschool children, the fact that children with hearing impairments are characterized by underdevelopment of all components of speech, as well as the presence of specific difficulties in the formation of logical thinking.